Strategi Pengembangan Peternakan Kambing di Kabupaten BatuBara - Patrizal, Patrizal; Hasnudi, Hasnudi; Lubis, Yusniar (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2021)
This study aims to determine the formulation of a goat farming business development strategy and alternative strategies for developing a goat farming business in Batubara Regency, which has been implemented from 4 February 2020 to 30 March 2020 in 3 Districts and 9 villages. The number of samples in this study were 85 people consisting of 79 men and 6 women. The sampling technique was stratified random sampling with a large, medium and small category of livestock population. The data analysis method used matrix analysis (IFE), matrix (EFE), and matrix (SWOT). The results showed that the formulation of strategies that can be used in the development of goats is to maintain and maintain the existing growth stabilization (hold and maintain) with priority strategies. increase community motivation to raise goats, increase the availability of infrastructure and livestock health officers. The results of the analysis using the IFE and EFE matrices show that internal factors are classified as strong and breeders are able to take advantage of their strengths to overcome their weaknesses. In addition, strong external factors can avoid threats by taking advantage of existing opportunities.